Pengaruh Green Human Resource Management dan Green Supply Chain Management terhadap Kinerja Berkelanjutan - Akhmad Fatwa Abdullah; Aty Herawati (Jurnal Ketenagakerjaan, 2025)
PT. Industri Jamu dan Farmasi Sido Muncul Tbk (Sido Muncul) is one of the companies that implementing the Green Productivity concept. Using indicators of Green Productivity, namely Green Human Resource Management (GHRM) and Green Supply Chain Management (GSCM), this study aims to investigate the influence of GHRM and GSCM on sustainable performance at Sido Muncul, specifically focusing on the aspect of environmental performance. The research utilizes data collected from 100 respondents, all of whom are employees of Sido Muncul, during December 2024 and January 2025. The data analysis technique applied is path analysis using the Structural Equation Model (SEM) Partial Least Squares (PLS) method with the assistance of SmartPLS 4.0 software. The results of the direct hypothesis testing show a significant and positive influence of each latent variable. These findings indicate that the implementation of environmentally friendly practices in human resource management and supply chain management leads to improved sustainable performance. Furthermore, the indirect hypothesis testing reveals that the latent variables have a significant and positive indirect influence. These results demonstrate that environmental performance significantly and positively mediates the relationship between GHRM and GSCM and sustainable performance. This research contributes to the expanding literature on sustainable performance studies by emphasizing the importance of GHRM and GSCM practices, with the mediating role of environmental performance. Additionally, it provides valuable insights for companies aiming to implement Green Productivity, which can positively impact sustainable performance enhancement.